Explaining the choice overload effect from a self-determination perspective - Ong, Johnathan (2014)
The choice overload effect occurs when one is provided with an extensive choice set leading to negative effects such as poor performance and satisfaction. This counter-intuitive finding goes against the common notion that having more choice is generally better. However, some studies have failed to demonstrate the choice overload effect and suggested that the effect could be moderated by certain individual difference variables. This study examines the possible moderators of the choice overload effect from the perspective of the self-determination theory. Causality orientations (controlled & autonomous) were used to examine the choice overload effect. Sixty participants were randomly assigned to either the no choice condition, moderate choice condition (6 choices) or extensive choice condition (24 choices). Dependent variables included performance and satisfaction in an anagram task, and persistence and satisfaction in a tracing task. Results showed that the choice overload effect was absent and causality orientations did not moderate the effect of choice on outcomes.